2021
DOI: 10.2106/jbjs.cc.20.00374
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Presentation of Foramen Magnum Meningioma Masqueraded by Carpal Tunnel Syndrome

Abstract: Case: Meningioma is the second most common intracranial tumor. We present 2 cases of foramen magnum meningioma (FMM) that was first operated on with the diagnosis of carpal tunnel syndrome (CTS). Conclusion: During the diagnostic assessment of CTS and recalcitrant CTS, a more proximal etiology of nerve compression should be considered, including FMM. If a more proximal cause of nerve dysfunction is suspected, cervical spine magnetic resonance imaging ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 14 publications
(18 reference statements)
0
1
0
Order By: Relevance
“…However, foramen magnum meningioma is often misdiagnosed. Bahrami et al reported 2 cases of foramen magnum meningioma mistaken for carpal tunnel syndrome due to the similarity of symptoms [ 8 ]. Some reported cases of foramen magnum meningioma presented as occipital neuralgia, drop attacks, brainstem compression, and cervical myelopathy [ 5 , [9] , [10] , [11] ].…”
Section: Discussionmentioning
confidence: 99%
“…However, foramen magnum meningioma is often misdiagnosed. Bahrami et al reported 2 cases of foramen magnum meningioma mistaken for carpal tunnel syndrome due to the similarity of symptoms [ 8 ]. Some reported cases of foramen magnum meningioma presented as occipital neuralgia, drop attacks, brainstem compression, and cervical myelopathy [ 5 , [9] , [10] , [11] ].…”
Section: Discussionmentioning
confidence: 99%